1989
DOI: 10.1128/aac.33.12.2075
|View full text |Cite
|
Sign up to set email alerts
|

Binding and killing of bacteria by bismuth subsalicylate

Abstract: Bismuth subsalicylate (BSS) is a compound without significant aqueous solubility that is widely used for the treatment of gastrointestinal disorders. BSS was able to bind bacteria of diverse species, and these bound bacteria were subsequently killed. A 4-log10 reduction of viable bacteria occurred within 4 h after a 10 mM aqueous suspension of BSS was inoculated with 2 x 10(6) Escherichia coli cells per ml. Binding and killing were dependent on the levels of inoculated bacteria, and significant binding but lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 19 publications
(14 reference statements)
2
54
1
Order By: Relevance
“…Strain Tx-30a was also associated, again in contrast to the other two strains, with a significant reduction in intracellular iron levels following exposure to MIC CBS . Both of these results would be consistent with a loss of membrane integrity (44), leading to an accumulation of nonutilizable ATP in the extracellular medium and a concurrent loss of iron from the cell. We speculate that this effect may reflect the higher bismuth concentration needed to inhibit this strain and may also be linked to the incomplete reversal of bismuth-induced growth inhibition in the presence of protective iron.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Strain Tx-30a was also associated, again in contrast to the other two strains, with a significant reduction in intracellular iron levels following exposure to MIC CBS . Both of these results would be consistent with a loss of membrane integrity (44), leading to an accumulation of nonutilizable ATP in the extracellular medium and a concurrent loss of iron from the cell. We speculate that this effect may reflect the higher bismuth concentration needed to inhibit this strain and may also be linked to the incomplete reversal of bismuth-induced growth inhibition in the presence of protective iron.…”
Section: Discussionsupporting
confidence: 73%
“…Iron is required for growth because it is a cofactor for many essential enzymatic processes (42), and many of the observed effects of bismuth on bacteria could be the result of iron limitation. These effects include a reduction in intracellular ATP levels (44), inhibition of protein and cell wall synthesis and of membrane function (32), and a reduction in capsular polysaccharide production (19,20,22,28).…”
mentioning
confidence: 99%
“…A few studies from the 1980s-90s have demonstrated the antimicrobial effects of BSS on enteric pathogens, but the in-vitro antimicrobial data is not available for several important pathogens. [6][7][8][9] In addition, little attention was focused on the relative contribution of BiOCl, which is an additional form of bismuth in the small and large intestine where the pathogens would be residing. In comparison to the current MICs presented here, Cornick et al reported analogous MICs for BSS and SS on similar genera and species of bacteria, but MICs for BiOCl were not done.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 To help explain the effectiveness of BSS in relieving infectious diarrhea, in vitro experiments published in the 80s and 90s have demonstrated this active drug possesses antimicrobial properties against bacteria and viruses. [6][7][8][9] Along with BSS, other bismuth salts that form in the gastrointestinal (GI) tract elicit similar activity. As BSS passes through the stomach, it undergoes hydrolysis by stomach acid resulting in the release of salicylate that gets absorbed into the bloodstream while the bismuth remains in the GI tract forming other insoluble salts including bismuth oxychloride (BiOCl).…”
Section: Introductionmentioning
confidence: 99%
“…Aliquots of 1.0 ml were collected from the cultures periodically with sterile glass pipettes. Aliquots from the bismuth subsalicylate culture were diluted 1:1 with 1 M disodium tartaric acid (Acros Organics B.V.B.A, Geel, Belgium) to solubilize undissolved bismuth subsalicylate (41). The optical density at 600 nm (OD 600 ) of each aliquot was determined immediately after collection, and readings were plotted versus time.…”
Section: Methodsmentioning
confidence: 99%